2018
DOI: 10.1159/000491546
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Management of Children and Adolescents with Chronic Myeloid Leukemia: The Italian Experience

Abstract: Background: To date, no data on the adherence to specific guidelines for children with chronic myeloid leukemia (CML) in chronic phase (CP) have been reported. Methods: Since 2001, guidelines for treatment with imatinib mesylate (IM) and monitoring in patients younger than 18 years with CP-CML have been shared with 9 pediatric referral centers (P centers) and 4 reference centers for adults and children/adolescents (AP centers) in Italy. In this study, the adherence to these guidelines was analyzed. Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…In all eligible patients (missing data from two patients), the CHR rate achieved by IMA treatment was 65% (n = 13/20). This rate is lower compared to previous reports with older children who achieved CHR in more than 95% of cases 22,23 . The proportion of children initially presenting in chronic phase and achieving CHR according to the ELN citeria at 3 months of therapy was 59% (n = 10/17).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In all eligible patients (missing data from two patients), the CHR rate achieved by IMA treatment was 65% (n = 13/20). This rate is lower compared to previous reports with older children who achieved CHR in more than 95% of cases 22,23 . The proportion of children initially presenting in chronic phase and achieving CHR according to the ELN citeria at 3 months of therapy was 59% (n = 10/17).…”
Section: Discussioncontrasting
confidence: 61%
“…reported 46% and 61% CCyR rate at 6 and 12 months, respectively, in newly diagnosed CML patients treated with IMA 260 mg/sqm/day 23 . The Italian experience administering a daily IMA dosage of 340 mg/m 2 resulted in a 29.6 % CCyR rate at 3 months 22 . However, none of the children in the current study achieved CCyR earlier than 4 months after initiation of IMA treatment.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…An improved conditioning regimen of allogeneic-HSCT with reduced-intensity stem cell transplantation could minimize the post-transplant mortality (19). Since CML remains a rare, but also a debilitating disease in the paediatric population, guidelines for treating paediatric CML need to be continuously optimized and incorporate the therapeutic experience stemming from adult CML (27). Clinical experience from the adult population may guide the therapeutic decision making process, however, care should be taken in terms of drug formulation, pharmacokinetics and compliance when applying the treatment to the fragile paediatric age group (28).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that imatinib therapy in CML is associated with a low incidence of VZV infection, does not disseminate, responds well to therapy, and does not mandate a recommendation for herpes zoster prophylaxis in patients with CML [ 32 ]. In pediatric trials of imatinib, no unusual cases of VZV infection were reported [ 8 , 9 , 33 ]. This is in contrast to the experience with other pediatric cancers or other diseases requiring immunosuppressive therapies, which have the risk for a potentially fatal course of VZV infection.…”
Section: Effect Of Tki On Immune Functionmentioning
confidence: 99%